Event-Driven Microservices for Autonomous Supply Chain Coordination: A Technical Deep Dive - Venkata Anil Kumar Nilisetty (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of event-driven microservices architecture in supply chain management represents a transformative shift from traditional monolithic systems. This technical exploration presents an innovative framework for autonomous supply chain coordination that addresses the challenges of modern logistics and distribution networks. The architecture combines advanced event processing, distributed tracing, and machine learning capabilities to create resilient, scalable supply chain solutions. Through the implementation of circuit breakers, CQRS patterns, and sophisticated monitoring systems, organizations can achieve enhanced operational efficiency, reduced downtime, and improved fault tolerance. The framework incorporates real-time inventory tracking, automated supplier management, intelligent demand forecasting, and anomaly detection mechanisms. The deployment strategy leverages containerization and orchestration technologies to ensure optimal resource utilization and system reliability. This comprehensive solution demonstrates significant improvements in order fulfillment, inventory accuracy, and system responsiveness while maintaining high availability and scalability across distributed environments.